Characterization and Application of Transition-Metal Dichalcogenides with Rapid Second Harmonic Generation Imaging - 김영철 (The Graduate School, Ajou University, 2024)
Second harmonic generation (SHG) imaging has been formulated and extended to investigate the nonlinear properties and crystallography in transition-metal dichalcogenides (TMDs). This thesis delves deeply into the exploration and understanding of transition-metal dichalcogenides (TMDs) layers using rapid second harmonic generation (SHG) imaging. Our investigation process using rapid SHG imaging led us to the characterization of these TMD layers, focusing particularly on aspects of crystallinity such as orientation and homogeneity. A noteworthy observation was made regarding the twisted bilayer MoS2. In this thesis, we unraveled a complex relationship between the intensity of SHG and the twist angle. A further in-depth examination of this relationship was carried out by examining the effects of strong interlayer coupling, which were substantiated by measurements of photoluminescence (PL). In our research, we observed the in situ processing of bilayer MoS2 using femtosecond laser ablation techniques. By mapping out critical threshold behaviors, we pinpointed optimal laser processing conditions essential for precise layer-by- layer manipulation of TMDs. This revelation of laser-induced thresholds became instrumental in the precise control of TMDs, opening doors to potential advancements in optoelectronic device fabrication. One of the most groundbreaking findings was the transformative role of bacteria on SHG signals in monolayer MoS2 flakes. There was an anisotropic enhancement of SHG in the presence of single-celled bacteria on monolayer TMD, with strain effects caused by bacteria. This discovery not only magnifies SHG imaging sensitivity to biomaterial strains on the surfaces but also introduces a promising frontier in harnessing this phenomenon for innovative optical and optoelectronic devices. Finally, as a result of our research, we have been able to provide an innovative approach to the detection and identification of different types of microbial. By capturing transient SHG signals during the cell rupture process, we were successful in discerning different bacterial species. This proficiency introduces a revolutionary path to label-free detection in single cells, thereby augmenting the toolkit for enhanced diagnostic procedures. In summary, this research propounds significant advancements in our comprehension of TMDs, enriching the potential applications of SHG imaging in both the scientific and technological landscapes.
학위논문(박사)--에너지시스템학과,2024. 2
Keywords: label-free sensing; laser thinning; microbial strain; second harmonic generation; transition-metal dichalcogenides